Implementasi Pendekatan Taktis dalam meningkatkan Motivasi Belajar Futsal - Oman Hadiana (PUSAT SAINS INDONESIA, 2020)
The purpose of this study was to determine the effectiveness of the implementation of tactical approaches to futsal learning motivation. The method used was an experiment with a randomized posttest-only control group design. The sample consisted of 62 PJKR students in the second semester of the academic year 2018/2019 even semester STKIP Muhammadiyah Kuningan, 30 students as an experimental group who were treated with a tactical approach, and 32 control groups using a traditional approach. Cluster random sampling technique. The instrument used to measure motivation uses the questionnaire Situational Motivation Scale (SIMS). The results showed that the group given the tactical approach was more effective than the group given the traditional approach to futsal learning motivation. Students are more motivated because the tactical approach presents fun and exhilarating learning. Further research is needed to explore the application of tactical approaches to futsal playing skills.